Thin infrared high-reflection mirror and preparation method thereof

By using a synergistic design of magnetron sputtering and NH3 etching, a thin infrared high-reflectivity mirror with a Ni-Ti alloy film was fabricated, solving the problem of the thickness and weight of traditional infrared mirrors and meeting the requirements of high-performance and lightweight infrared optical systems.

CN121700346APending Publication Date: 2026-03-20YANGZHOU XIAGUANG OPTICAL ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511950298.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-23
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

In the existing technology, traditional glass reflectors are thick and heavy, and the infrared high reflectivity mirrors based on Ti alloys have problems such as poor interface bonding, complex process, high cost and low film density during the preparation process, which makes it difficult to meet the requirements of high precision and lightweight.

Method used

By employing magnetron sputtering technology combined with NH3 active group etching and composition gradient design, a thin infrared high-reflectivity mirror with strong film bonding, high density, and good surface quality was prepared by depositing a Ni-Ti alloy film on a Ti alloy substrate and using stepped sputtering power density and vacuum annealing.

Benefits of technology

It has achieved high-performance manufacturing of thin infrared high-reflectivity mirrors with moderate film thickness, high interfacial bonding strength, and good surface finish, making them suitable for lightweight, high-performance infrared optical systems in aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121700346A_ABST
    Figure CN121700346A_ABST
Patent Text Reader

Abstract

The invention discloses a thin infrared high-reflection mirror and a preparation method thereof, and belongs to the technical field of optical devices. The preparation method comprises the following steps: depositing a Ni-Ti alloy film on a heated Ti alloy substrate in a deposition atmosphere in which Ar gas and a small amount of NH3 gas are introduced by adopting a radio frequency magnetron co-sputtering process and taking a Ti target and a Ni target as sources; the Ni target sputtering power is increased in a stepped mode, so that the Ni content in the film layer is gradually increased from the interface to the surface, and a component gradient structure is formed; and carrying out vacuum annealing and polishing treatment after deposition. Through the etching effect of the NH3 active group and the component gradient structure design, the internal stress of the film layer is synergistically reduced, the density and the interface bonding force are improved, and the obtained reflector has the advantages of moderate film layer thickness, firm bonding, high surface quality and easy processing, and is suitable for light-weight and high-performance infrared optical systems in the fields of aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of optical device manufacturing technology, and particularly relates to a thin infrared high reflectivity mirror and a preparation method thereof. BACKGROUND

[0002] In the fields of aerospace, national defense technology and infrared photoelectric detection, a high reflectivity mirror is a core component of an optical imaging system, and the performance of the high reflectivity mirror directly determines the resolution, imaging quality and reliability of the system. With the increasing requirement for detection sensitivity of the system, the demand for large-aperture reflectivity mirrors is increasing. However, in order to meet the strength requirement, the traditional glass reflectivity mirror is usually thick and heavy, and is prone to deformation under the action of gravity, which is difficult to meet the high-precision surface shape requirement.

[0003] Titanium (Ti) alloy is considered to be an ideal lightweight mirror substrate material due to its high specific strength, low density, low thermal expansion coefficient and good thermal stability. At present, there are two technical routes for the infrared high reflectivity mirror based on Ti alloy: One is a composite optical reflectivity mirror (Ti alloy / thermocompression bonding glass type) prepared by thermocompression bonding glass on the surface of the Ti substrate. However, since the bonding is performed between metal and non-metal, the interface bonding property and thermal stress still need to be solved, and the process technology is complex and the cost is high. Meanwhile, this composite technology cannot fundamentally solve the problem of large thickness and heavy weight of the traditional glass reflectivity mirror. The other is a coated reflectivity mirror prepared by depositing a film layer on the surface of the Ti substrate. However, since it is difficult to achieve the quality requirement of the optical surface by the optical polishing process on the surface of the Ti alloy, a thick film layer (hundreds of microns thick) is deposited by electroplating, and then the surface is optically polished. However, the film layer prepared by the traditional electroplating thick film (Ti alloy / electroplating thick film type) has defects such as low density, low interface bonding force, large thickness and difficult to control, and a large amount of surface optical polishing is required in the later stage. In addition, the electroplating process has the problems of large pollution and high energy consumption, and the production is often limited due to energy saving and environmental protection problems.

[0004] As an advanced thin film deposition technology, magnetron sputtering has the advantages of dense film layer, good bonding force and controllability. However, when it is directly used to prepare a metal alloy reflectivity film layer with a thickness of several microns to tens of microns, it still faces technical bottlenecks such as easy peeling of the film layer due to internal stress accumulation, low deposition rate, and difficulty in balancing the density and surface finish of the thick film.

[0005] Therefore, it is urgent to develop a new preparation process and a corresponding reflectivity mirror product to overcome the shortcomings of the prior art and realize reliable manufacturing of a high-performance, lightweight thin infrared high reflectivity mirror. SUMMARY

[0006] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a thin infrared high-reflectivity mirror and its preparation method. This invention can prepare a thin infrared high-reflectivity mirror with strong film bonding, high density, good surface quality, and easy processing.

[0007] The technical solution adopted by this invention to solve its technical problem is: A method for fabricating a thin infrared high-reflectivity mirror specifically includes the following steps: Step S1: Provide a polished Ti alloy substrate and clean it; Step S2: Place the cleaned Ti alloy substrate in a magnetron sputtering vacuum chamber, evacuate to a high vacuum, and heat the Ti alloy substrate to 280℃~320℃; Step S3: Introduce a deposition atmosphere composed of Ar gas and NH3 gas into the vacuum chamber; Step S4: Turn on the RF power supply of Ti target and Ni target for pre-sputter cleaning, wherein the sputtering power density of Ti target is 7W / cm²~10W / cm² and the sputtering power density of Ni target is 5W / cm²~15W / cm². Step S5: After pre-sputtering, co-sputtering deposition begins, with a deposition time of 5h to 7h. During the deposition process, the sputtering power density of the Ti target is kept constant, and the sputtering power density of the Ni target is increased stepwise, so that the Ni content in the formed Ni-Ti alloy film gradually increases from the interface of the Ti alloy substrate to the surface of the film along the thickness direction. Step S6: After deposition, the Ti alloy substrate with the Ni-Ti alloy film is subjected to vacuum annealing. Step S7: Polish the surface of the annealed Ni-Ti alloy film.

[0008] This invention reduces internal stress in the film layer and improves density and interfacial adhesion through the etching effect of NH3 active groups and the design of compositional gradient structure. The resulting reflector has the advantages of moderate film thickness, strong adhesion, high surface quality and easy processing, and is suitable for lightweight, high-performance infrared optical systems in aerospace and other fields.

[0009] Furthermore, in step S5, the process of progressively increasing the sputtering power density of the Ni target specifically includes: First stage: Sputter at a power density of 5W / cm² to 7W / cm² for 10 minutes; Second stage: Increase the power density to 7W / cm²~9W / cm², sputter for 10min~15min; Third stage: Increase the power density to 9W / cm²~11W / cm², sputter for 10min~15min; Fourth stage: Increase the power density to 10W / cm²~13W / cm², sputter for 15min~20min; Fifth stage: Increase the power density to 12W / cm²~14W / cm² and sputter for 15 minutes; Stage 6: Maintain the power density at 12W / cm² to 15W / cm² and sputter for 4 to 6 hours.

[0010] The above operations, by gradually increasing the sputtering power density of the Ni target, enable the technical effect of "compositional gradient" (smoothing interfacial stress and enhancing adhesion) to be achieved stably and repeatedly, and provide a specific power-time path for obtaining the best film performance.

[0011] Furthermore, in step S2, the high vacuum condition is ≤3×10⁻⁶. -4 A vacuum level of Pa. This vacuum condition ensures the cleanliness of the deposition chamber and effectively reduces the contamination of the film by residual gases (such as oxygen and water vapor). It is an important prerequisite for obtaining a high-purity, low-defect, and highly dense film, and a fundamental guarantee for improving the optical performance and reliability of the final reflector.

[0012] Further, in step S3, the total pressure of the deposition atmosphere is adjusted to 0.1 Pa to 0.25 Pa; the Ar gas flow rate in the deposition atmosphere is 40 sccm to 60 sccm, and the NH3 gas flow rate is 1.5 sccm to 3 sccm. This optimized range of parameters represents the best balance between the NH3-assisted effect (active groups etching weakly bonded atoms and improving the mobility of deposited atoms) and stable sputtering plasma, which is beneficial for improving deposition rate, reducing film roughness, and enhancing film density.

[0013] Furthermore, in step S6, the vacuum annealing process is performed as follows: First stage: In a vacuum environment, the temperature is raised from room temperature to 300℃ and held for 30 minutes; Second stage: Increase the temperature from 300℃ to 350℃ and hold for 30 minutes; Second stage: Raise the temperature from 350℃ to 400℃ and keep it at that temperature for 3 hours.

[0014] The above annealing process effectively eliminates lattice defects and internal stresses accumulated during the deposition process, while promoting atomic interdiffusion at the film-substrate interface. This maximizes the interfacial bonding strength and the structural stability of the film itself without damaging the film structure.

[0015] Furthermore, in the first stage, the temperature is raised from room temperature to 300°C over a period of 40 minutes. In the second stage, the temperature is increased from 300℃ to 350℃, and the heating time is 10 minutes. In the third stage, the temperature is increased from 350℃ to 400℃, and the heating time is 10 minutes.

[0016] The heating rate at each stage is limited. Controlling the heating rate avoids new thermal stress caused by drastic temperature changes, ensuring a smooth and controllable annealing process. This allows the film and substrate to uniformly and coordinately complete stress release and structural relaxation, representing a refined process control for achieving high-quality annealing results. Furthermore, in step S7, polishing is performed using a combination of diamond abrasive grinding and polishing with a polishing slurry. This combined polishing process, combining diamond abrasive grinding and polishing with a polishing slurry, optimizes the characteristics of the resulting dense and uniform Ni-Ti alloy film. This polishing method efficiently and controllably reduces the surface roughness of the film to nanometer-level optical requirements, demonstrating the excellent processability of the film of this invention.

[0017] A thin infrared high reflectivity mirror is prepared by the above-described preparation method; the thin infrared high reflectivity mirror includes a Ti alloy substrate and a compositionally graded Ni-Ti alloy reflective film layer formed on the Ti alloy substrate.

[0018] Furthermore, the thickness of the composition-gradient Ni-Ti alloy reflective film is 8 μm to 17.5 μm, and its surface roughness is ≤1.68 nm. The thickness of 8 μm to 17.5 μm indicates its "thin" characteristic, sufficient to achieve high reflectivity while avoiding the stress and processing difficulties caused by excessive thickness. The surface roughness of ≤1.68 nm directly quantifies the ultra-high optical surface quality achieved by the final product, a key performance indicator for high-resolution infrared imaging systems.

[0019] Furthermore, the atomic percentage of Ni in the Ni-Ti alloy reflective film gradually increases from the Ti alloy substrate interface toward the film surface.

[0020] The beneficial effects of this invention are as follows: This invention has a reasonable design and a simple preparation method, and has the following advantages: (1) Process innovation and synergistic effect: In this invention, a small amount of NH3 gas is introduced into the magnetron sputtering deposition atmosphere. The active hydrogen and nitrogen groups generated by the decomposition of NH3 in the plasma can perform in-situ etching and stripping of Ni and Ti atoms that are not firmly bound during the deposition process, which plays the role of "in-situ cleaning" and activating the surface of the fossil substrate. This process, combined with the heated substrate, significantly improves the surface mobility of the deposited atoms, thereby effectively improving the deposition rate and density of the film, and reducing internal stress and surface roughness. (2) Gradual composition structure design: By stepwise control of Ni target power, a continuous gradual change in composition (Ni content increases from interface to surface) of Ni-Ti alloy film in the thickness direction is achieved. This gradient composition design can smooth out the abrupt change in physical properties (such as thermal expansion coefficient and lattice constant) at the interface, greatly alleviate the stress at the film / substrate interface, fundamentally enhance the film-substrate bonding force, and make the thick film less prone to peeling during subsequent polishing and use; (3) Excellent comprehensive performance: The method of this invention combines NH3-assisted etching, composition gradient design and optimized process parameters (gas pressure, temperature and power) to solve the problems of stress, density and bonding force in thick film deposition. The prepared mirror has the advantages of moderate film thickness (8~17.5µm), dense structure, high interface bonding strength and good surface finish (easy to polish to nanoscale roughness). At the same time, the whole process is clean and environmentally friendly. (4) High product reliability: The final product is a composite structure of "Ti alloy / composition gradient Ni-Ti alloy film", which combines the advantages of Ti alloy substrate being lightweight and high-strength with the excellent infrared reflection performance and mechanical properties of Ni-Ti alloy film. It is suitable for aerospace infrared optical systems with extremely high requirements for weight, surface accuracy and reliability. Attached Figure Description

[0021] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0023] Figure 1 This is a scanning electron micrograph of the composition-gradient Ni-Ti alloy thick film prepared in Example 1; Figure 2 This is a scanning electron micrograph of the surface of a compositionally graded Ni-Ti alloy thick film prepared in Example 2; Figure 3 This is a scanning electron micrograph of the composition-gradient Ni-Ti alloy thick film prepared in Example 3; Figure 4 These are atomic force micrographs of the Ti alloy substrate after polishing in Example 3; Figure 5 This is an atomic force micrograph of the surface of the composition-gradient Ni-Ti alloy thick film obtained in Example 3 before polishing; Figure 6This is an atomic force micrograph of the surface of a compositionally graded Ni-Ti alloy thick film after polishing, prepared in Example 3; Figure 7 These are surface profilometer photographs of the compositionally graded Ni-Ti alloy thick films prepared in Example 3, taken during a tribological test. Figure 8 This is a scanning electron micrograph of the surface of a Ni-Ti alloy thick film with a compositional gradient prepared in Comparative Example 1. Figure 9 This is a surface profilometer photograph of the compositionally graded Ni-Ti alloy thick film prepared in Comparative Example 2, used in a friction and wear test. Detailed Implementation

[0024] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0025] It should be noted that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the exemplary implementations according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this description, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] In a first aspect, the present invention provides a method for fabricating a thin infrared high-reflectivity mirror, specifically comprising the following steps: Step S1: Provide a polished Ti alloy substrate and clean it; Step S2: Place the cleaned Ti alloy substrate in a magnetron sputtering vacuum chamber, evacuate to a high vacuum, and heat the Ti alloy substrate to 280℃~320℃; Step S3: Introduce a deposition atmosphere composed of Ar gas and NH3 gas into the vacuum chamber; Step S4: Turn on the RF power supply of Ti target and Ni target for pre-sputter cleaning, wherein the sputtering power density of Ti target is 7W / cm²~10W / cm² and the sputtering power density of Ni target is 5W / cm²~15W / cm². Step S5: After pre-sputtering, co-sputtering deposition begins, with a deposition time of 5h to 7h. During the deposition process, the sputtering power density of the Ti target is kept constant, and the sputtering power density of the Ni target is increased stepwise, so that the Ni content in the formed Ni-Ti alloy film gradually increases from the interface of the Ti alloy substrate to the surface of the film along the thickness direction. Step S6: After deposition, the Ti alloy substrate with the Ni-Ti alloy film is subjected to vacuum annealing. Step S7: Polish the surface of the annealed Ni-Ti alloy film.

[0028] In step S5, the process of gradually increasing the sputtering power density of the Ni target specifically includes: First stage: Sputter at a power density of 5W / cm² to 7W / cm² for 10 minutes; Second stage: Increase the power density to 7W / cm²~9W / cm², sputter for 10min~15min; Third stage: Increase the power density to 9W / cm²~11W / cm², sputter for 10min~15min; Fourth stage: Increase the power density to 10W / cm²~13W / cm², sputter for 15min~20min; Fifth stage: Increase the power density to 12W / cm²~14W / cm² and sputter for 15 minutes; Stage 6: Maintain the power density at 12W / cm² to 15W / cm² and sputter for 4 to 6 hours.

[0029] In step S2, the high vacuum condition is ≤3×10 -4 Vacuum degree in Pa.

[0030] In step S3, the total pressure of the deposition atmosphere is adjusted to 0.1 Pa to 0.25 Pa; in the deposition atmosphere, the Ar gas flow rate is 40 sccm to 60 sccm, and the NH3 gas flow rate is 1.5 sccm to 3 sccm. In step S6, the vacuum annealing process is performed as follows: First stage: In a vacuum environment, the temperature is raised from room temperature to 300℃ and held for 30 minutes; Second stage: Increase the temperature from 300℃ to 350℃ and hold for 30 minutes; Second stage: Raise the temperature from 350℃ to 400℃ and keep it at that temperature for 3 hours.

[0031] In the first stage, the temperature is raised from room temperature to 300℃ in 40 minutes; In the second stage, the temperature is increased from 300℃ to 350℃, and the heating time is 10 minutes. In the third stage, the temperature is increased from 350℃ to 400℃, and the heating time is 10 minutes.

[0032] In step S7, polishing is performed by combining diamond abrasive grinding with polishing liquid.

[0033] Secondly, the present invention also provides a thin infrared high reflectivity mirror, which is prepared by the above-described method; the thin infrared high reflectivity mirror includes a Ti alloy substrate and a composition-gradient Ni-Ti alloy reflective film layer formed on the Ti alloy substrate. The thickness of the composition-gradient Ni-Ti alloy reflective film layer is 8 μm to 17.5 μm, and its surface roughness is ≤1.68 nm.

[0034] In the compositionally graded Ni-Ti alloy reflective film, the atomic percentage of Ni gradually increases from the interface of the Ti alloy substrate towards the surface of the film.

[0035] The biggest bottlenecks in thick metal films are high internal stress, low density, weak interfacial adhesion, low deposition rate, and small thickness. Firstly, this invention gradually increases the Ni target sputtering power, causing the Ni content in the film to gradually increase from the interface along the thickness direction, forming a compositionally graded Ni-Ti alloy thick film. This effectively reduces interfacial stress. Further annealing further increases the interfacial adhesion, ensuring the Ni-Ti alloy thick film will not peel off or fail during subsequent polishing and use. Secondly, this invention introduces a small amount of NH3 gas into the thin film deposition chamber. Through discharge, it generates highly corrosive active groups, thereby corroding and stripping loosely bonded Ni and Ti atoms within the film during deposition in real time, improving the activity of the deposition surface. Further control of process parameters such as sputtering power density, gas pressure, and substrate temperature effectively increases the diffusion activity of adsorbed Ni and Ti atoms on the deposition surface, ultimately improving the deposition rate of the Ni-Ti alloy thick film, increasing the film density, reducing internal stress, and lowering the surface roughness.

[0036] Example 1 A method for fabricating a thin infrared high-reflectivity mirror specifically includes the following steps: Step 1: Cleaning the Ti alloy substrate. The polished Ti alloy substrate is first rinsed with deionized water, then soaked in acetone and wiped with a lint-free cloth. Next, the substrate is ultrasonically cleaned with acetone and deionized water in sequence, and finally the substrate is dried.

[0037] Step 2: Prepare compositionally graded Ni-Ti alloy thick films using magnetron co-sputtering. Step 2.1: Mount the cleaned Ti alloy substrate onto the anode in the coating vacuum chamber, mount the Ni target onto one sputtering cathode in the coating vacuum chamber, and mount the Ti target onto the other sputtering cathode in the coating vacuum chamber; close the vacuum chamber and evacuate the background vacuum of the vacuum chamber to 3×10⁻⁶. -4 Pa; Heat the Ti alloy substrate to 320 °C; Step 2.2: Introduce NH3 gas into the vacuum chamber and adjust the NH3 gas flow rate to 3 sccm; introduce Ar gas into the vacuum chamber and adjust the Ar gas flow rate to 60 sccm; adjust the total gas pressure in the vacuum chamber to 0.25 Pa; Step 2.3: Turn on the Ti target RF power source and adjust the sputtering power density of the Ti target to 7 W / cm². 2 The Ti target was pre-sputtered and cleaned for 15 minutes; the Ni target RF power source was turned on, and the sputtering power density of the Ni target was adjusted to 5 W / cm². 2 Pre-sputter cleaning of the Ni target for 15 minutes; Step 2.4: Set the Ti target sputtering time to 7 hours; set the Ni target sputtering power density to 5 W / cm³. 2 (10 min) → 7 W / cm 2 (15min) → 9W / cm 2 (15min) → 10W / cm 2 (20 min) → 12 W / cm 2 (6h); Open the baffles of the Ti target and Ni target, and begin depositing a compositionally graded Ni-Ti alloy thick film; Step 2.5: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0038] Step 3: Vacuum annealing treatment of the "Ti alloy / Ni-Ti alloy film" reflector. Step 3.1: Place the "Ti alloy / Ni-Ti alloy film" reflector into the vacuum annealing furnace, and evacuate the furnace to a vacuum level of 3×10⁻⁶. -4 Pa; Step 3.2: Set the annealing process according to the annealing regime and begin annealing. The annealing process is as follows: from room temperature to 300℃, heat for 40 minutes → hold at 300℃ for 30 minutes → heat for 10 minutes to 350℃ → hold at 350℃ for 30 minutes → heat for 10 minutes to 400℃ → hold at 400℃ for 3 hours. Step 3.3: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0039] Step 4: Polish the Ni-Ti alloy film in the annealed "Ti alloy / Ni-Ti alloy film" reflector. The polishing process involves fine grinding with W5 diamond abrasive, followed by polishing with a special polishing liquid.

[0040] Figure 1 This is a scanning electron micrograph of the composition-gradient Ni-Ti alloy thick film prepared in this embodiment. As shown in the figure, the profilometer test results indicate that the film thickness is 8.8 µm. The thick film has a dense structure, uniform grains, and a smooth surface.

[0041] Example 2 A method for fabricating a thin infrared high-reflectivity mirror specifically includes the following steps: Step 1: Cleaning the Ti alloy substrate. The polished Ti alloy substrate is first rinsed with deionized water, then soaked in acetone and wiped with a lint-free cloth. Next, the substrate is ultrasonically cleaned with acetone and deionized water in sequence, and finally the substrate is dried.

[0042] Step 2: Prepare compositionally graded Ni-Ti alloy thick films using magnetron co-sputtering. Step 2.1: Mount the cleaned Ti alloy substrate onto the anode in the coating vacuum chamber, mount the Ni target onto one sputtering cathode in the coating vacuum chamber, and mount the Ti target onto the other sputtering cathode in the coating vacuum chamber; close the vacuum chamber and evacuate the background vacuum of the vacuum chamber to 3×10⁻⁶. -4 Pa; Heat the Ti alloy substrate to 300 ℃; Step 2.2: Introduce NH3 gas into the vacuum chamber and adjust the NH3 gas flow rate to 2 sccm; introduce Ar gas into the vacuum chamber and adjust the Ar gas flow rate to 50 sccm; adjust the total gas pressure in the vacuum chamber to 0.15 Pa; Step 2.3: Turn on the Ti target RF power source and adjust the sputtering power density of the Ti target to 8.5 W / cm². 2 The Ti target was pre-sputtered and cleaned for 15 minutes; the Ni target RF power source was turned on, and the sputtering power density of the Ni target was adjusted to 6 W / cm². 2 Pre-sputter cleaning of the Ni target for 15 minutes; Step 2.4: Set the Ti target sputtering time to 6 hours; set the Ni target sputtering power density to 6 W / cm³. 2 (10 min) → 8 W / cm 2 (10 min) → 10 W / cm 2 (10 min) → 11 W / cm 2 (15min) → 12W / cm 2 (15min) → 13W / cm 2 (5h); Open the baffles of the Ti target and Ni target, and begin depositing a compositionally graded Ni-Ti alloy thick film; Step 2.5: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0043] Step 3: Vacuum annealing treatment of the "Ti alloy / Ni-Ti alloy film" reflector. Step 3.1: Place the "Ti alloy / Ni-Ti alloy film" reflector into the vacuum annealing furnace, and evacuate the furnace to a vacuum level of 3×10⁻⁶. -4 Pa; Step 3.2: Set the annealing process according to the annealing regime and begin annealing. The annealing process is as follows: from room temperature to 300℃, heat for 40 minutes → hold at 300℃ for 30 minutes → heat for 10 minutes to 350℃ → hold at 350℃ for 30 minutes → heat for 10 minutes to 400℃ → hold at 400℃ for 3 hours. Step 3.3: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0044] Step 4: Polish the Ni-Ti alloy film in the annealed "Ti alloy / Ni-Ti alloy film" reflector. The polishing process involves fine grinding with W5 diamond abrasive, followed by polishing with a special polishing liquid.

[0045] Figure 2 This is a scanning electron micrograph of the composition-gradient Ni-Ti alloy thick film prepared in this embodiment. The figure shows that the profilometer test results indicate the film thickness is 13.6 µm. From... Figure 2 It can be seen that as the film thickness increases, the grains of the thick film grow, but the thick film still has a dense structure, uniform grains, and a smooth surface.

[0046] Example 3 A method for fabricating a thin infrared high-reflectivity mirror specifically includes the following steps: Step 1: Cleaning the Ti alloy substrate. The polished Ti alloy substrate is first rinsed with deionized water, then soaked in acetone and wiped with a lint-free cloth. Next, the substrate is ultrasonically cleaned with acetone and deionized water in sequence, and finally the substrate is dried.

[0047] Step 2: Prepare compositionally graded Ni-Ti alloy thick films using magnetron co-sputtering. Step 2.1: Mount the cleaned Ti alloy substrate onto the anode in the coating vacuum chamber, mount the Ni target onto one sputtering cathode in the coating vacuum chamber, and mount the Ti target onto the other sputtering cathode in the coating vacuum chamber; close the vacuum chamber and evacuate the background vacuum of the vacuum chamber to 3×10⁻⁶. -4 Pa; Heat the Ti alloy substrate to 280℃; Step 2.2: Introduce NH3 gas into the vacuum chamber and adjust the NH3 gas flow rate to 1.5 sccm; introduce Ar gas into the vacuum chamber and adjust the Ar gas flow rate to 40 sccm; adjust the total gas pressure in the vacuum chamber to 0.1 Pa; Step 2.3: Turn on the Ti target RF power source and adjust the sputtering power density of the Ti target to 10 W / cm². 2 The Ti target was pre-sputtered and cleaned for 15 minutes; the Ni target RF power source was turned on, and the sputtering power density of the Ni target was adjusted to 7 W / cm². 2 Pre-sputter cleaning of the Ni target for 15 minutes; Step 2.4: Set the Ti target sputtering time to 5 hours; set the Ni target sputtering power density to 7 W / cm³. 2 (10 min) → 9 W / cm 2 (10 min) → 11 W / cm 2 (10 min) → 13 W / cm 2 (15min) → 14W / cm 2 (15min) → 15W / cm 2 (4h); Open the baffles of the Ti target and Ni target, and begin depositing a compositionally graded Ni-Ti alloy thick film; Step 2.5: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0048] Step 3: Vacuum annealing treatment of the "Ti alloy / Ni-Ti alloy film" reflector. Step 3.1: Place the "Ti alloy / Ni-Ti alloy film" reflector into the vacuum annealing furnace, and evacuate the furnace to a vacuum level of 3×10⁻⁶. -4 Pa; Step 3.2: Set the annealing process according to the annealing regime and begin annealing. The annealing process is as follows: from room temperature to 300℃, heat for 40 minutes → hold at 300℃ for 30 minutes → heat for 10 minutes to 350℃ → hold at 350℃ for 30 minutes → heat for 10 minutes to 400℃ → hold at 400℃ for 3 hours. Step 3.3: After the temperature drops to room temperature in the vacuum, turn off the vacuum and remove the sample.

[0049] Step 4: Polish the Ni-Ti alloy film in the annealed "Ti alloy / Ni-Ti alloy film" reflector. The polishing process involves fine grinding with W5 diamond abrasive, followed by polishing with a special polishing liquid.

[0050] Figure 3This is a scanning electron micrograph of the composition-gradient Ni-Ti alloy thick film prepared in this embodiment. The figure shows that the profilometer test results indicate the film thickness is 17.3 µm. It can be seen that the grains in this thick film continue to grow, and while the grain size is not entirely uniform, the structure remains dense, and the surface is smooth.

[0051] Figure 4 This is an atomic force micrograph of the Ti alloy substrate after polishing in this embodiment. As can be seen from the figure, the Ti alloy has a relatively large surface roughness of 31.3 nm, indicating that the Ti alloy itself is difficult to polish.

[0052] Figure 5 This is an atomic force micrograph of the surface of the composition-gradient Ni-Ti alloy thick film obtained in this embodiment before polishing. As can be seen from the figure, the surface roughness of the composition-gradient Ni-Ti alloy thick film is reduced to 8.6 nm, indicating that the film layer grown by the process of this invention is uniform and has the ability to "fill" the roughness of the Ti alloy substrate.

[0053] Figure 6 This is an atomic force micrograph of the surface of the composition-gradient Ni-Ti alloy thick film prepared in this embodiment after polishing. As can be seen from the figure, after polishing, the surface roughness of the composition-gradient Ni-Ti alloy thick film is further reduced to 1.68 nm, indicating that the composition-gradient Ni-Ti alloy thick film prepared by this invention is easier to polish and is beneficial for processing high-reflectivity mirrors with extremely high optical quality surfaces.

[0054] The Ni-Ti alloy thick film prepared in this embodiment was subjected to friction and wear tests using a friction and wear testing machine. Figure 7 This is a surface profilometer photograph from a friction and wear test. The image shows that within the friction zone of the grinding head, the Ni-Ti alloy thick film suffers severe damage, resulting in deep wear pits. In the non-friction zone, the Ni-Ti alloy thick film remains intact, maintaining a dense structure and a smooth, uniform surface. The boundaries between the friction and non-friction zones are clearly defined, with sharp edges. This indicates that the Ni-Ti alloy thick film prepared in this invention has a strong interfacial bond with the Ti alloy substrate, low internal stress, and no delamination or peeling occurs during the friction process.

[0055] Comparative Example 1 The difference from Example 1 is that in step 2.2, only Ar gas was used during the deposition of this comparative example, and no NH3 gas was added.

[0056] Figure 8 This is a scanning electron micrograph of the surface of a Ni-Ti alloy thick film with a compositional gradient prepared in this comparative example. The image shows that the film exhibits high internal stress, poor adhesion to the substrate, and cracking.

[0057] Comparative Example 2 The difference from Example 1 is that step three, vacuum annealing of the "Ti alloy / Ni-Ti alloy film" reflector, is omitted in this comparative example.

[0058] Figure 9 This is a surface profilometer photograph of the tribological wear test of the compositionally graded Ni-Ti alloy thick film prepared in this comparative example. The image shows wear marks at the center of the friction area, with obvious bulges appearing outside the wear marks, indicating that the film peeled off from the substrate under external force during the friction process.

[0059] In summary, this invention successfully fabricates a thin-film infrared high-reflectivity mirror with a Ti alloy / composition-gradient Ni-Ti alloy film by introducing NH3-assisted etching and a magnetron sputtering process with composition gradient design. This mirror exhibits strong substrate-film bonding, dense film layers, low internal stress, high surface finish, and ease of processing, demonstrating superior overall performance and meeting the requirements of high-end infrared optical systems for lightweight, high precision, and high reliability.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for fabricating a thin infrared high-reflectivity mirror, characterized in that: Specifically, the steps include the following: Step S1: Provide a polished Ti alloy substrate and clean it; Step S2: Place the cleaned Ti alloy substrate in a magnetron sputtering vacuum chamber, evacuate to a high vacuum, and heat the Ti alloy substrate to 280℃~320℃; Step S3: Introduce a deposition atmosphere composed of Ar gas and NH3 gas into the vacuum chamber; Step S4: Turn on the RF power supply of Ti target and Ni target for pre-sputter cleaning, wherein the sputtering power density of Ti target is 7W / cm²~10W / cm² and the sputtering power density of Ni target is 5W / cm²~15W / cm². Step S5: After pre-sputtering, co-sputtering deposition begins, with a deposition time of 5h to 7h. During the deposition process, the sputtering power density of the Ti target is kept constant, and the sputtering power density of the Ni target is increased stepwise, so that the Ni content in the formed Ni-Ti alloy film gradually increases from the interface of the Ti alloy substrate to the surface of the film along the thickness direction. Step S6: After deposition, the Ti alloy substrate with the Ni-Ti alloy film is subjected to vacuum annealing. Step S7: Polish the surface of the annealed Ni-Ti alloy film.

2. The method for preparing a thin infrared high-reflectivity mirror according to claim 1, characterized in that: In step S5, the process of gradually increasing the sputtering power density of the Ni target specifically includes: First stage: Sputter at a power density of 5W / cm² to 7W / cm² for 10 minutes; Second stage: Increase the power density to 7W / cm²~9W / cm², sputter for 10min~15min; Third stage: Increase the power density to 9W / cm²~11W / cm², sputter for 10min~15min; Fourth stage: Increase the power density to 10W / cm²~13W / cm², sputter for 15min~20min; Fifth stage: Increase the power density to 12W / cm²~14W / cm² and sputter for 15 minutes; Stage 6: Maintain the power density at 12W / cm² to 15W / cm² and sputter for 4 to 6 hours.

3. The method for preparing a thin infrared high-reflectivity mirror according to claim 1, characterized in that: In step S2, the high vacuum condition is ≤3×10 -4 Vacuum degree in Pa.

4. The method for preparing a thin infrared high-reflectivity mirror according to claim 1, characterized in that: In step S3, the total pressure of the deposition atmosphere is adjusted to 0.1 Pa to 0.25 Pa; the Ar gas flow rate is 40 sccm to 60 sccm and the NH3 gas flow rate is 1.5 sccm to 3 sccm.

5. The method for preparing a thin infrared high-reflectivity mirror according to claim 1, characterized in that: In step S6, the vacuum annealing process is performed as follows: First stage: In a vacuum environment, the temperature is raised from room temperature to 300℃ and held for 30 minutes; Second stage: Increase the temperature from 300℃ to 350℃ and hold for 30 minutes; Second stage: Raise the temperature from 350℃ to 400℃ and keep it at that temperature for 3 hours.

6. The method for preparing a thin infrared high-reflectivity mirror according to claim 5, characterized in that: In the first stage, the temperature is raised from room temperature to 300°C in 40 minutes; In the second stage, the temperature is increased from 300℃ to 350℃, and the heating time is 10 minutes. In the third stage, the temperature is increased from 350℃ to 400℃, and the heating time is 10 minutes.

7. The method for preparing a thin infrared high-reflectivity mirror according to claim 1, characterized in that: In step S7, polishing is performed by combining diamond abrasive grinding with polishing liquid.

8. A thin infrared high reflectivity mirror, characterized in that: The thin infrared high reflectivity mirror is prepared by the preparation method described in any one of claims 1 to 7; The thin infrared high reflectivity mirror includes a Ti alloy substrate and a compositionally graded Ni-Ti alloy reflective film layer formed on the Ti alloy substrate.

9. A thin infrared high-reflectivity mirror according to claim 8, characterized in that: The thickness of the compositionally graded Ni-Ti alloy reflective film is 8μm to 17.5μm, and its surface roughness is ≤1.68nm.

10. A thin infrared high-reflectivity mirror according to claim 8 or 9, characterized in that: The atomic percentage of Ni in the Ni-Ti alloy reflective film gradually increases from the Ti alloy substrate interface toward the film surface.